(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
For any academic library to remain relevant to the changing information needs of its users, it has to do an assessment of the utilization of its services by its users and how such utilization satisfies information needs. Thus, this descriptive- correlational research was conducted to provide the academic library of a private university in Cagayan de Oro City with valuable information as to the quality of its services and collections as perceived by the college students. Specifically, this research determined the student users’ assessment of the quality of library services, extent of use of the library collections, satisfaction of their information needs, and any significant assocaition between the quality of library services and utilization and between utilization and satisfaction of information needs. Data were collected using validated and pilot-tested questionnaires, which responses were processed using descriptive and inferential statistics. As found in this research, the quality of library services was assessed to be very good and the library materials were used to a high extent, except for the non-print materials. Moreover, the student users’ academic and non-academic information needs were satisfied. The tests of relationship revealed a signicant association between the library’s quality of services and utilization and between the student users’ satisfaction of information needs and utilization of the library. Therefore, efforts to improve further the quality of library services should be instituted to increase utilization and to achieve maximum satisfaction of the library users’ information needs.